FACTORS OF OCCURRENCE AND DYNAMICS OF MARITAL CONFLICTS (Psychology Travelogs, 2024)
The article is devoted to the study of the problem of emergence and development of marital conflicts, as well as to the identification of the main factors contributing to their emergence. In the context of socio-economic changes, which are often accompanied by crisis phenomena in society, the problem of family conflicts is becoming particularly relevant. The article examines the key aspects that determine the nature of family disputes, including the complexity of communications, differences in values, beliefs and upbringing of partners, as well as external and internal stress factors that can worsen mutual understanding between spouses.The author analyses various theoretical approaches to the classification of family conflicts and cites research by psychologists such as V. Sysenko, S. Kovalev, N. Grishina and others, who emphasise the role of conflicts as a natural part of family interaction. Conflicts can be both negative and constructive, as they often create opportunities for developing and strengthening relationships through the discovery of new ways of understanding and problem solving.The reasons for conflicts are systematised, in particular: restriction of freedom of action, misunderstandings due to different perceptions of family roles, material difficulties, sexual disharmony, infidelity, lack of respect, jealousy and bad habits. At the same time, the stages of conflict development, from the latent phase to the culminating and final stage, are considered, with an emphasis on the role of emotions and psychological factors in this process.Particular attention is paid to the impact of external factors, such as economic difficulties, social status of partners and general level of stress, which can worsen family interaction. The article also mentions the classification of conflicts according to various parameters, in particular, depending on the subjects of the conflict, sources and behaviour of the participants.The purpose of the work is to study in depth the causes of marital conflicts and identify effective ways to prevent and overcome them. The author emphasises that constructive communication, mutual understanding and the ability to adapt in crisis situations are important for the harmonious development of family relations.
Keywords: conflict; marital conflicts; spouses; marital relations; causes of conflicts; communication; stages of conflict; conflicts in the family; ways of resolving conflicts